2019
DOI: 10.3389/fimmu.2019.02924
|View full text |Cite
|
Sign up to set email alerts
|

Loss of Dkk-1 in Osteocytes Mitigates Alveolar Bone Loss in Mice With Periodontitis

Abstract: Background: Periodontitis is a highly prevalent infection-triggered inflammatory disease that results in bone loss. Inflammation causes bone resorption by osteoclasts, and also by suppression of bone formation via increase of Dickkopf-1 (Dkk-1), an inhibitor of Wnt signaling. Here, we tested the hypothesis that osteocytic Dkk-1 is a key factor in the pathogenesis of periodontitis-induced alveolar bone loss (ABL). Methods: Twelve-week-old female mice with a constitutive deletion of Dkk-1 specifically in osteocy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 34 publications
1
19
0
Order By: Relevance
“…However, Cre+ mice were largely protected from this effect. Interestingly, serum CTX did not reflect the histological increase in osteoclast numbers, similar to our findings in healthy Dkk1-deficient mice, suggesting that Dkk1 rather affects osteoclast numbers than osteoclast activity 23 , 54 . Inhibition of Dkk1 has already been associated with suppressed bone resorption.…”
Section: Discussionsupporting
confidence: 78%
“…However, Cre+ mice were largely protected from this effect. Interestingly, serum CTX did not reflect the histological increase in osteoclast numbers, similar to our findings in healthy Dkk1-deficient mice, suggesting that Dkk1 rather affects osteoclast numbers than osteoclast activity 23 , 54 . Inhibition of Dkk1 has already been associated with suppressed bone resorption.…”
Section: Discussionsupporting
confidence: 78%
“…On the other hand, in osteocyte-specific Dkk1-deficient mice, the expression of TCF-7 remained at the control level, and the expression of LEF-1 was not changed compared to WT mice. In this study, Dkk-1 derived from osteocytes played a crucial role in alveolar bone loss in periodontitis [69].…”
Section: Osteocytesmentioning
confidence: 71%
“…Stimulated macrophages, DCs, and T cells promote the expression level of RANKL in periodontal ligament cells and osteoblasts through their corresponding pro-inflammatory cytokines so as to initiate bone resorption performed by osteoclasts, with OPG being degraded as well (Tsukasaki, 2020), resulting in reduced RANKL/OPG ratio, which leads to alveolar bone lesion even tooth loss. Nowadays, there are more and more advanced researches focusing on the potential key molecule or signaling pathway targeted at regulating osteoimmune microenvironment in periodontitis (Goes et al, 2019;Li et al, 2020;, which may provide novel perspectives and contribute to the therapeutic approaches for periodontitis based on osteoimmunomodulation. For instance, in a recent study, Wu et al (2020) revealed the new AKT2/c-Jun N-terminal kinase (JNK)1/2/c-jun and AKT2/miR-155-5p/DET1/c-Jun signaling pathways that played a role in altering macrophage polarization and regulating periodontitis inflammation and AKT2 promoted M2 polarization of macrophages, suggesting a novel strategy for periodontitis treatment.…”
Section: Periodontitismentioning
confidence: 99%